Uji Fetotoksisitas Ekstrak Daun Kemangi (Ocimum Sanctum L.) pada Mencit Putih - A, Almahdy; Yandri, Marina (Jurnal Sains dan Teknologi Farmasi, 2010)
The fetotoxicity effect of  methanolic extract  of the leaf of  kemangi (Ocimum Sanctum L.) on mice had been studied. The extract was given orally at various doses of 50, 100, and 200 mg/kg BW at 6th Â until 15th day of pregnancy. On the 18th day of  pregnancy laparactomy was perpormed on half number of fetuses from each litter. Mice on  doses of 500 mg/kg BW showed abortion. Macroscopic observation on the fetuses showed some anomalis of body weight compared to control but there was no malformation occured at all doses.